Clinical findings in 33 subjects with large supernumerary marker(15) chromosomes and 3 subjects with triplication of 15q11-q13 - Dennis, N.R.; Veltman, M.W.M.; Thompson, R.; Craig, E.; Bolton, P.F.; Thomas, N.S. (American journal of medical genetics. Part A, 2006)
We present clinical data on 33 subjects with additional copies of the Prader‐Willi‐Angelman critical region (PWACR) contained in a supernumerary marker chromosome (SMC). Twenty‐three subjects had a typical large non‐mosaic SMC(15) containing two copies of the PWACR. They showed a variable but generally severe phenotype of learning disability and autism, with seizures in approximately two‐thirds. The other 10 differed from this typical pattern in respect of mosaicism, variation in copy number, or arrangement of the PWACR within the SMC or number of SMC per cell. Clinical severity increased with the number of additional copies of the PWACR and decreased with mosaicism for a normal cell line. There was a trend for a larger number of seizures to be associated with more severe learning disability. Three subjects with interstitial triplications of 15q11‐q13 showed a range of phenotypes similar to those of the typical large SMC(15). All additional copies of the PWACR in this series were maternally‐derived. FISH and molecular data localizing the breakpoints of the rearrangements have been previously published or are included in this report. No correlations were found between specific clinical features and variations in breakpoints proximal and distal to the PWACR. © 2006 Wiley‐Liss, Inc.